Good Visual Acuity Outcome from an Ocular Blast Injury with Proper Management in Dr. Soetomo General Hospital Surabaya, Indonesia - Rifat Nurfahri; Delfitri Lutfi; Ismi Zuhria (Department of Ophthalmology, Faculty of Medicine, Universitas Airlangga, 2021)
Introduction: Ocular blast injury related to fireworks most often causing corneal erosion (29%), conjunctival erosion (11%), and conjunctival foreign body (10%) with children are more often than adults (65.9%:34.1%), and males far more often than female (71.9%:28.1%). Knowing proper management is very important to achieve the best result. Case presentation: We describe an ocular blast injury that experienced broad erosion and multiple foreign bodies on the corneal and pericorneal surface in the left eye and visual acuity decreased. The foreign body was scattered, and the fluorescein test was positive. We did proper foreign body extraction, irrigation, and ocular bandage. It was treated with chloramphenicol 0.5% eye ointment and homatropine eye drop. In two months, the patient’s left eye had clear cornea with a small scar formation near the visual axis. The visual acuity was 6/7 and BCVA was 6/6 with S-0.5 C-0.5 A 50° correction. Conclusions: Patients with ocular blast injury limited to superficial cornea erosion and and conjunctival erosion have a reasonable probability of achieving the best visual acuity. Foreign body extraction, proper irrigation, and topical medication show promising results. Scar formation near the visual axis can disrupt visual acuity however can be corrected in this case it can be corrected with glasses. Furthermore, public promotion and regulation to control firework using are very important.